The Role of Interdisciplinary Collaboration in App-Development for Aquaculture - Abdullah, Ahmad Zakki; Muljono, Pudji; Sarwoprasodjo, Sarwititi; Amanah, Siti (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Pembangunan Nasional Veteran Jakarta, 2025)
This study explores app-development supporting Indonesia's fisheries digital ecosystem, aligned with the National Medium-Term Development Plan (2020-2024) that emphasizes digitalization to strengthen agriculture and fisheries. Focusing on interdisciplinary collaboration and group communication, the research examines how these elements influence the design and effectiveness of ICT for development (ICT4D). A qualitative case study approach was used, data collected from observations and interviews with app-developers in startups and the aquaculture community. The interview analysis follows two coding cycles: the first examines interdisciplinary collaboration and group communication dynamics and knowledge integration, while the second focuses on technology's impact on aquaculture practices. Findings reveal key categories—communication frequency and quality, role clarification, and knowledge management—vital to effective collaboration. Communication barriers can be mitigated through conflict resolution and training, while knowledge integration boost aquaculture efficiency and productivity. Applying structuration theory, this study shows how innovation-supportive organizational structures enhance individual agency, while rigid policies can stifle creativity. This research contributes to ICT4D literature by providing insights into collaboration strategies and organizational dynamics that influence technology development in traditional sectors, offering a framework for similar digital initiatives.